RISK MANAGEMENT AND PERFORMANCE OF FINANCIAL INSTITUTIONS IN NIGERIA: EVIDENCE FROM FINANCIAL FIRMS IN ILORIN - Emmanuel Imuede Oyasor (J-MACC, 2025)
The financial sector is an integral part of the economy, playing a vital role in the overall economic development of a nation, but financial institutions in this sector face a myriad of risks. The risk management process consists of a series of steps, which are establishing the context, identifying, analyzing, assessing, treating, monitoring and communicating risks, which allow continuous improvement of decision making. Hence, the purpose of this study is to examine the impact of risk management on the performance of financial institutions, a case study of some selected financial institutions in Ilorin Kwara State. Additionally, this study employed the survey method with a qualitative approach and the population is 530 of which the sample of 273 questionnaires was distributed among the respondents which comprise of the staffs of Access Bank, Stanbic IBTC Bank and GTCO Bank branches in Ilorin Metropolis. However, a total of 242 copies of questionnaires was successfully filled and returned for analysis. This study therefore utilized simple regression in data analysis with the aid of statistical package for social sciences (SPSS) version 20. Consequently, this study reveals that risk transfer has significant relationship with financial performance in some selected banks in Ilorin, Kwara State with 0.000 level of significance. The study also discovered that risk selection has significant impact on financial performance of some selected banks in some selected banks in Ilorin, Kwara State in with 0.000 level of significance. Hence, this study therefore recommends that Access Bank, Stanbic IBTC Bank and GTCO Bank and other financial institutions manage its risk effectively in such a way that transparency and reduced loss can be achieved; with this the organizations will be able to secure higher return of investment and reduced potential risk. Also, financial firms should consider assumption of loss responsibilities in order to limit higher losses from a given risk, as this will generate an expected return and financial productivity. It was also suggested that the Access Bank, Stanbic IBTC Bank and GTCO Bank and other financial institutions should secure adequate reserves to manage potential credit loses, as this will them to achieve financial health and business stability in the long run. .